2015
DOI: 10.2172/1235570
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Regulatory Cost and Quality Expectations. An Exploration of Technical Change in Minimum Efficiency Performance Standards

Abstract: The dual purpose of this project was to contribute to basic knowledge about the interaction between regulation and innovation and to inform the cost and benefit expectations related to technical change which are embedded in the rulemaking process of an important area of national regulation. The area of regulation focused on here is minimum efficiency performance standards (MEPS) for appliances and other energy-using products. Relevant both to U.S. climate policy and energy policy for buildings, MEPS remove cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Taylor, Spurlock and Yang (2015) assessed minimum efficiency performance standards (MEPS) set by the Department of Energy (DOE) for five appliance types – room air conditioners, refrigerators–freezers, dishwashers, clothes washers, and clothes dryers. The authors compare the observed ex post appliance prices and performance with the ex ante engineering-cost analyses developed in the RIAs.…”
Section: Review Of the Retrospective Analysis Case Studiesmentioning
confidence: 99%
“…Taylor, Spurlock and Yang (2015) assessed minimum efficiency performance standards (MEPS) set by the Department of Energy (DOE) for five appliance types – room air conditioners, refrigerators–freezers, dishwashers, clothes washers, and clothes dryers. The authors compare the observed ex post appliance prices and performance with the ex ante engineering-cost analyses developed in the RIAs.…”
Section: Review Of the Retrospective Analysis Case Studiesmentioning
confidence: 99%
“…For instance, in the United States, this is due to the statutory requirement in the Energy Policy and Conservation Act (EPCA) that revisions to the Minimum Energy Performance Standards (MEPS) be "technically feasible and economically justified." Prices of higher-efficiency equipment decline over time in various markets as higher-efficiency equipment is produced at scale (Taylor et al, 2015;Abhyankar et al, 2017;Spurlock, 2014). Similar methodologies have been used to a more limited degree to support energy efficiency standards processes in countries such as India, China, Ghana, Mexico, etc.…”
Section: Summary Of the Methodologymentioning
confidence: 99%
“…To determine the incremental price paid by consumers, we first have to estimate what the price would have been in the absence of the efficiency improvement (counterfactual price). Examples in Japan and Korea discussed above and examples in several other countries for other appliances and equipment indicate that efficiency policies and efficiency improvements do not increase inflation-adjusted prices over time and may in fact reduce prices compared to the counterfactual prices (Taylor, Spurlock, & Yang, 2015;Van Buskirk, Kantner, Gerke, & Chu, 2014). However, at any given point in time, prices of efficient ACs appear to be higher than prices for conventional ACs, and engineering estimates also indicate that at any given point in time, it costs more to produce efficient ACs.…”
Section: Net Consumer Benefitmentioning
confidence: 99%